Post-exercise recovery (ASPETAR Sports Medicine Journal, 2014)
Präsentation verschiedener Methoden zur Wiederherstellung nach sportlicher Belastung inkl. eines Videos zu einer Diskussionsrunde mit den Autoren der folgenden Beiträge: Post-exercise recovery • Electrostimulation recovery-related strategies • Recovery nutrition for the Arabic athlete competing in team based sports • Sleep as a recovery tool for elite athletes • Recovery techniques for athletes • Optimising recovery in sport: psychological considerations • Football recovery strategies • Post-game recovery strategies in youth football • Sleep & sporting performance